Five Years of Full-Scale War in Ukraine: New Realities and Chances for Peace - Bordas, Maria; Tomolya, Janos (European Scientific Journal, ESJ, 2026)
The war between Russia and Ukraine, which began in 2014, is still ongoing, and it is very difficult to predict when and how it will end. The Russian invasion, which began in 2022, has been going on for over 1,500 days. This study analyses the structural transformation of the geopolitical landscape and shifting international mediation dynamics as the Ukraine conflict enters its fifth year of full-scale war. The paper examines two critical external variables driving the current dynamic. First, it analyses the dual role of the United States, which has transitioned from an external supporter into an active, structural stakeholder whose domestic political fluctuations directly dictate the frontline’s operational boundaries, thereby disqualifying Washington as a neutral mediator in the eyes of the Kremlin. Second, the study evaluates China’s strategy of constructive ambiguity; Beijing leverages its economic and technological lifeline to Moscow while simultaneously marketing non-Western peace proposals—co-authored with Global South actors—to project an alternative global governance model. It evaluates two potential pathways, a "Korean Peninsula Model" of de facto partition and an "Armed Neutrality" of a non-NATO, Western-secured fortress. Moreover, this essay concludes that lasting peace requires a new global security architecture beyond a simple ceasefire line.